On the Documental Basis of A. Blok’s Essay “Poslednie dni Imperatorskoi vlasti” (“The Last Days of Imperial Power”) - Alexandr S. Alexandrov (Studia Litterarum)
This work is devoted to issues related to commenting on the first chapter of the essay “The Last Days of Imperial Power” — “The State of Power.” The introduction briefly outlines the main stages of Block’s work in the Extraordinary Investigative Commission “to investigate the illegal actions of former ministers, chief executives and other senior officials of both civil and military and naval departments.” The paper presents an analysis of individual portraits of government officials, derived in the first chapter, and notes the sources of hidden and direct quotations. Characteristics from “The Last Days…” are compared with Blok’s portrait sketches from his notebooks, diaries and notes based on the protocols of interrogations of former representatives of the tsarist government. The article also presents unknown archival materials from the Manuscript Department of the Pushkin House.